ORGANIZATION OF TRAINING ON THE TRANSFER OF REQUIREMENTS AND NORMS OF THE HEALTH TEST (Scientific journal of the Fergana State University, 2025)
In this article, health tests are used to determine the physical development and physical fitness of the population, and to form a habit of systematically performing physical exercises for a healthy lifestyle.